THE INFLUENCE OF TIKTOK CONTENT @BUIRAMIRA ON THE EASE OF FINAL-YEAR STUDENTS AT THE STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA - Annisa fadillah; Ainisa Putri; Dhea Fitriana; Uchie; Samsul Bahri Pasaribu; Nursapia Harahap (OPINI: Journal of Communication and Social Science, 2025)
This study investigates the influence of TikTok content from the account @buiramira on the ease experienced by final-year students at the State Islamic University of North Sumatra (UINSU) in completing their final projects. “Students’ ease” is measured through respondents’ perceptions of how easily they can find information, understand the material, and apply the tips provided in @buiramira’s content. Using a quantitative method with questionnaires distributed to 50 Communication Science students at UINSU (based on Slovin’s formula with a 10% margin of error), the data were analyzed using simple linear regression, correlation, coefficient of determination, and t-tests. The results indicate a significant influence of @buiramira’s content on students’ ease (p < 0.05), with a contribution of 46.4%. This study concludes that educational content on TikTok can serve as a valuable source of information for students in completing their final projects and highlights the importance of delivering content that is clear, accurate, and easy to understand.